2008
DOI: 10.1603/0022-0493(2008)101[927:iortpi]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of Resistance to Pyriproxyfen in <I>Bemisia tabaci</I> (Hemiptera: Aleyrodidae) Males and Females (B Biotype)

Abstract: We evaluated effects of the insect growth regulator pyriproxyfen on Bemisia tabaci (Gennadius) (B biotype) (Hemiptera: Aleyrodidae) males and females in laboratory bioassays. Insects were treated with pyriproxyfen as either eggs or nymphs. In all tests, the LC50 for a laboratory-selected resistant strain was at least 620 times greater than for an unselected susceptible strain. When insects were treated as eggs, survival did not differ between males and females of either strain. When insects were treated as nym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…As with every insecticide it is important to be cautious about using pyriproxyfen formulations as a stand-alone intervention since tolerance to pyriproxyfen has been found in Diptera [87,88]. It is also of concern to know whether the progeny of gravid females that are exposed to sub-lethal level doses of pyriproxyfen and survive have greater tolerance to pyriproxyfen than other mosquitoes.…”
Section: Discussionmentioning
confidence: 99%
“…As with every insecticide it is important to be cautious about using pyriproxyfen formulations as a stand-alone intervention since tolerance to pyriproxyfen has been found in Diptera [87,88]. It is also of concern to know whether the progeny of gravid females that are exposed to sub-lethal level doses of pyriproxyfen and survive have greater tolerance to pyriproxyfen than other mosquitoes.…”
Section: Discussionmentioning
confidence: 99%
“…The overuse of pesticides and rapid development of resistance in B. tabaci has been shown to cause high abundance and change the identity of the common B. tabaci species in other cropping systems around the world (e.g. Crowder et al , 2008). For example, a shift from B. tabaci MEAM1 species to MED species was found in cotton fields in Israel and this change in species composition had an impact on resistance to insecticides, with one population showing less resistance to insect growth regulators (Horowitz & Ishaaya, 2014).…”
Section: Other Factors and Hypothesesmentioning
confidence: 99%
“…If insecticide use increases in the coming years, such as in vegetable crops in or near cassava, or in cassava itself, there is the potential for B. tabaci species attacking cassava to be exposed to strong resistance selection pressures. Experiences in cotton production landscapes elsewhere have shown that resistance can develop quickly in B. tabaci (Crowder et al , 2008; Gnankine et al , 2013) and studies should consider establishing baseline levels of resistant alleles in populations now. Furthermore, the testing and development of products based on newer chemistries, which have less non-target impacts, needs to be conducted in East Africa.…”
Section: Other Factors and Hypothesesmentioning
confidence: 99%